Pengaruh Penambangan Batu Terhadap Komunitas Makrozoobentos di Sungai Logawa - Eti Wahyuningsih; Nur Laila Rahayu; Musyarif Zaenuri (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the macrozoobenthic community, the effect of rock mining on the macrozoobenthic community, and the water quality of the Logawa River. The research method used is purposive random sampling technique at 5 stations with 3 replications. The results showed that species richness, individual abundance and diversity were low at several stations because not all macrozoobenthos had a tolerance value for living in waters where sediment conditions had been affected by rock mining. Meanwhile, the dominance index value of the high category at station 3 was due to the effects of rock mining which caused macrozoobenthos who were intolerant of rock mining to move, so that only macrozoobenthos that were resistant to such conditions survived and dominated the area. Water quality for macrozoobenthos is still quite good based on the measurement results.